Analysis of Serum Ferritin Levels in Pregnant Women with Gestational Diabetes Mellitus versus Healthy Pregnant Women: A Cross-sectional Study - Farzana Mustafa; H Mahesha Navada (National Journal of Laboratory Medicine)
Introduction: Gestational Diabetes Mellitus (GDM) is a disease that is linked to a variety of disturbances in the carbohydrate metabolism, specifically recognised during pregnancy. It is crucial to detect gestational diabetes at an early onset because if the developing foetus is exposed to abnormal carbohydrate metabolism can lead to morbidity, such as macrosomia and unexplained Intrauterine Death (IUD). Aim: To compare serum ferritin levels in pregnant women with and without GDM. Materials and Methods: This was a cross-sectional study conducted at Father Muller Medical College Hospital, Mangaluru, Karnataka, India, from December 2018 to July 2020. Antenatal patients were studied under two groups: those diagnosed with GDM (test group) during routine antenatal check-ups (n=62) and another group of non GDM antenatal mothers (n=62). Serum ferritin levels from venous blood were estimated for both GDM and non GDM mothers between 24 and 34 weeks of gestation and analysed for the association between the groups using t-test. Results: The mean gestational age was 30.85±2.51 weeks in the GDM group and 30.23±2.29 weeks in the non GDM group (p=0.1744). The mean Body Mass Index (BMI) in the GDM group was significantly higher (25.06±1.55 kg/m2) compared to the non GDM group (24.73±1.81 kg/m2) (p=0.0023). Haemoglobin levels were similar between groups (p=0.3610). Serum ferritin was significantly higher in the GDM group (33.14 ng/mL) compared to the non GDM group (30.18 ng/mL) (p=0.003). Conclusion: The GDM is likely associated with higher serum ferritin levels compared to non GDM mothers. The increase in ferritin levels appeared to be independent of haemoglobin status. However, the high levels of ferritin observed in GDM group could be linked to higher BMI values rather than higher blood glucose levels. This indicates that serum ferritin levels in GDM mothers may be due to maternal fat and obesity, serving as an inflammatory marker.